ANALISIS PERBANDINGAN OBLIGASI SYARIAH DENGAN OBLIGASI KONVENSIONAL BERDASARKAN YIELD TO MATURITY (YTM), CURRENT YIELD (CY) DAN TINGKAT RESIKO OBLIGASI PADA BURSA EFEK INDONESIA - B51111016, Darman Syahni (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This research aimed to compare between the Sharia bonds and Conventional bonds based on the value of Yield to Maturity (YTM) and Current Yield (CY). In addition to measuring the comparison of the bonds based its yields, this research also compared the risk level of bonds based on bond rating. Therefore, the findings of this research are expected to give a positive contribution in the from of useful information for information for investors to make investment decision. The objects of this research were the Sharia and Conventional bonds listed on the indonesia Stock Exchange (IDX) from 2010 to 2014. The analysis technique used was the analysis of t-test for two independent samples, whereas the analysis process used the IBM SPSS Statistics 20 for Windows. Based on the research findings, the equal variances assumed were 2.982 with a significance of .079, so it can be concluded that there was no significant difference between Sharia bonds and Conventional bonds based on the value Yield to Maturity (YTM), it indicated that investors holding both Sharia bonds and Conventional bonds until the maturity date, would receive almost equal yield. The Current Yield (CY) with equal variances assumed was -.033 with a significance of .107, so it can be concluded that that there was no significant difference between Sharia bonds and Conventional bonds. It showed that the market’s response to the issuance of Sharia bonds and Conventional bonds was relatively the same. Mean while, the comparison of the risk of both types of bonds indicated that the equal variances assumed were 2.601 with a significance of .630. this indicated that there was no significant difference, but absolutely the risk level of sharia bonds was greater than conventional bonds. Keywords: Indonesia Stock Exchange (IDX), SPSS 20, Yield to Maturity (YTM), current Yield (CY).